CFET Beyond 3 nm: SRAM Reliability Under Design-Time and Run-Time Variability - Sufia Shahin; Swati Deshwal; Anirban Kar; Mahdi Benkhelifa; Yogesh S. Chauhan; Hussam Amrouch (IEEE Journal on Exploratory Solid-State Computational Devices and Circuits)
This work investigates the reliability of complementary field-effect transistors (CFETs) by addressing both design-time variability arising from process variations and run-time variability due to temperature and aging effects. A rigorously calibrated TCAD model, validated against experimental CFET data, is employed to quantify the impact of metal gate granularity (MGG)-induced work-function variation (WFV) and random dopant fluctuation (RDF) on key device parameters, including the threshold voltage ( $V_{\mathrm {TH}}$ ), on-state current ( $I_{\mathrm {ON}}$ ), and off-state current ( $I_{\mathrm {OFF}}$ ). Temperature-dependent variability is systematically analyzed to further elucidate the behavior of these advanced devices. To capture the dynamic effects of aging, the reaction-diffusion (RD) framework—which accounts for defect generation due to negative bias temperature instability (NBTI)—is implemented in TCAD, enabling detailed modeling of trap generation and the corresponding $V_{\mathrm {TH}}$ shifts in p-type transistors under varying gate stress biases ( $V_{\mathrm {GSTR}}$ ) and operating temperatures. At the circuit level, a full array of 6T-static random access memory (SRAM) cells with the requisite peripheral circuits is simulated using SPICE after careful calibration of the industry-standard compact model of gate-all-around (BSIM-CMG) against the TCAD data. The variability analysis reveals that the access disturb margin achieves a cell sigma ( $\mu /\sigma $ ) of 17.4 at nominal supply voltage, significantly exceeding the $6\sigma $ robustness criterion for read disturbances. Moreover, as the operating temperature increases from 300 to 398 K, the read static noise margin (RSNM) and hold static noise margin (HSNM) degrade by 13.7% and 6.37%, respectively, while the write static noise margin (WSNM) improves by 18.3%. These findings provide critical insights into the design tradeoffs and reliability challenges of CFET-based SRAMs.